Synergistic induction of lipid catabolism and anti-inflammatory lipids in white fat of dietary obese mice in response to calorie restriction and n-3 fatty acids - Flachs, P; Rühl, R; Hensler, M; Janovska, P; Zouhar, P; Kus, V; Macek Jilkova, Z; Papp, E; Kuda, O; Svobodova, M; Rossmeisl, M; Tsenov, G; et al. (Diabetologia, 2011)
AIMS/HYPOTHESIS: Calorie restriction is an essential component in the treatment of obesity and associated diseases. Long-chain n-3 polyunsaturated fatty acids (LC n-3 PUFA) act as natural hypolipidaemics, reduce the risk of cardiovascular disease and could prevent the development of obesity and insulin resistance. We aimed to characterise the effectiveness and underlying mechanisms of the combination treatment with LC n-3 PUFA and 10% calorie restriction in the prevention of obesity and associated disorders in mice. METHODS: Male mice (C57BL/6J) were habituated to a corn-oil-based high-fat diet (cHF) for 2 weeks and then randomly assigned to various dietary treatments for 5 weeks or 15 weeks: (1) cHF, ad libitum; (2) cHF with LC n-3 PUFA concentrate replacing 15% (wt/wt) of dietary lipids (cHF + F), ad libitum; (3) cHF with calorie restriction (CR; cHF + CR); and (4) cHF + F + CR. Mice fed a chow diet were also studied. RESULTS: We show that white adipose tissue plays an active role in the amelioration of obesity and the improvement of glucose homeostasis by combining LC n-3 PUFA intake and calorie restriction in cHF-fed mice. Specifically in the epididymal fat in the abdomen, but not in other fat depots, synergistic induction of mitochondrial oxidative capacity and lipid catabolism was observed, resulting in increased oxidation of metabolic fuels in the absence of mitochondrial uncoupling, while low-grade inflammation was suppressed, reflecting changes in tissue levels of anti-inflammatory lipid mediators, namely 15-deoxy-Δ(12,15)-prostaglandin J(2) and protectin D1. CONCLUSIONS/INTERPRETATION: White adipose tissue metabolism linked to its inflammatory status in obesity could be modulated by combination treatment using calorie restriction and dietary LC n-3 PUFA to improve therapeutic strategies for metabolic syndrome.
Keywords: bílá tuková tkáň; Docosahexaenoic Acids; Real-Time Polymerase Chain Reaction; metabolismus lipidů; Mice, Obese; Fatty Acids, Omega-3; omega-3 mastné kyseliny; Prostaglandin D2; dietní tuky; Energy Metabolism; energetický metabolismus; prostaglandin D2; imunohistochemie; dieta s vysokým obsahem tuků; myši; myši obézní; Adipose Tissue, White; Mice; kalorická restrikce; Immunohistochemistry; Lipid Metabolism; mužské pohlaví; zvířata; Caloric Restriction; Animals; kyseliny dokosahexaenové; Male; kvantitativní polymerázová řetězová reakce; Diet, High-Fat; Dietary Fats